Finance and Development, March 2005. (Finance and Development; Finance and Development, 2005)
This paper highlights that the current round of trade talks under the auspices of the World Trade Organization aims at better integrating developing countries-especially the small and poor ones-into the global trading system. For that reason, it was named the Doha Development Agenda when it was launched in late 2001. However, more than three years on, little progress has been made. It took a late July 2004 accord outlining 'negotiating frameworks' in agriculture and industrial products just to keep the talks afloat.